PENERAPAN MODEL PEMBELAJARAN INTERACTIVE CONCEPTUAL INTRUCTION UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII SMP NURUL ILMI BANYUASIN - Nur Baiti; Aida Imtihana; Nyimas Yunierti Prihatin (STKIP Subang, 2026)
Critical thinking skills are one of the key competencies students must possess to meet the demands of 21st-century learning. However, students’ critical thinking skills in Islamic Religious Education classes have not yet developed optimally because the learning process tends to be teacher-centered, resulting in limited student engagement in analyzing, discussing, and expressing opinions. This study aims to determine students’ critical thinking skills before and after the implementation of the Interactive Conceptual Instruction (ICI) learning model, as well as to determine the effect of implementing this model on the critical thinking skills of seventh-grade students at Nurul Ilmi Junior High School in Banyuasin. This study used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 24 seventh-grade students selected using purposive sampling. Data were collected through critical thinking ability tests in the form of pretests and posttests, then analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed that students’ critical thinking skills prior to the implementation of the ICI learning model were still in the “fair” category, with a pretest average of 69.79. After implementing the ICI learning model, students’ critical thinking skills improved, with an average posttest score of 85.83. The results of the Wilcoxon Signed-Rank Test yielded a Z-value of -4.564 with an Asymp. Sig. (2-tailed) of <0.001, indicating a significant difference in students’ critical thinking skills before and after the implementation of the ICI learning model. Thus, the Interactive Conceptual Instruction (ICI) learning model has been proven effective in improving the critical thinking skills of seventh-grade students at Nurul Ilmi Junior High School in Banyuasin.